Linguistic variations of Blaan in Soccsksargen Region: A variationist sociolinguistic study - Ojanola, Raleigh; Tarusan, Mary Ann (Technium Social Sciences Journal, 2023)
Understanding language variations opens a wider perspective to language enthusiasts in boosting sociolinguistic awareness as regards to the different ways of using the language in different language contexts. It provides people from different geographical locations of Blaan to understand the language and its use. The study aimed to describe the linguistic variations of Blaan language in the four (4) sociolinguistic contexts of Blaan in Soccsksargen Region, Mindanao, Philippines such as Sarangani Blaan (SBL) of Sarangani Province, Koronadal Blaan (KBL) of South Cotabato Province, Columbio Blaan (CBL) of Sultan Kudarat Province, and Tulunan Blaan (TBL) of Cotabato Province in terms of phonological variations, morphological variations, semantic variations, and syntactic variations. Labov’s (1966) variationist sociolinguistic framework was employed in describing the linguistic variations of Blaan which was qualitative in nature. The study was participated by purposively selected sixteen (16) research participants who were composed of Blaan elders and Blaan teachers. The findings of the study reveal ample linguistic variations in SBL, KBL, CBL, and TBL in terms of sound, word formation, meaning, and sentence structure. The phonological variations include the number of vowel phoneme production for /a/, /e/, /é/, /i/, /o/ and /u/, the use of accent marks on vowel phonemes, the number of accented and unaccented vowel phonemes, phonetic and phonological change, and phoneme addition. The morphological variations include differences on tense markers, degrees of comparison markers, and other morphological features of the lexical categories of Blaan. The semantic variations include words that have positive meanings in one context but have offensive meanings as compared to the other context. The syntactic variations include forming of yes-no questions in Blaan and the placement of question markers. The study concludes that variations of language, in the perspective of sociolinguistics, prove that language is indeed changing, evolving, and adapting to the sociolinguistic contexts of different language communities.